2019
DOI: 10.1097/pr9.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

An audit of paediatric pain prevalence, intensity, and treatment at a South African tertiary hospital

Abstract: Introduction: Pain in paediatric inpatients is common, underrecognised, and undertreated in resource-rich countries. Little is known about the status of paediatric pain prevention and treatment in low- and middle-income countries. Objectives: This audit aimed to describe the prevalence and severity of pain in paediatric patients at a tertiary hospital in South Africa. Method: A single-day prospective observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…In previous studies, hospitalized children most frequently reported that worst pain was caused by needle pokes with prevalence of 34-40%, followed by surgery or trauma/injury. 14,31 This proportion was observed to vary between the clinical units in our study, lower in the ED where worst pain from acute illness/infection was more common and higher on the MS where needle pain accounted for nearly all worst-pain experiences.…”
Section: Pain Prevalencementioning
confidence: 65%
See 4 more Smart Citations
“…In previous studies, hospitalized children most frequently reported that worst pain was caused by needle pokes with prevalence of 34-40%, followed by surgery or trauma/injury. 14,31 This proportion was observed to vary between the clinical units in our study, lower in the ED where worst pain from acute illness/infection was more common and higher on the MS where needle pain accounted for nearly all worst-pain experiences.…”
Section: Pain Prevalencementioning
confidence: 65%
“…In similar studies on in-patient pediatric units, documentation rates for pain assessments and treatments during a 24-hour audit ranged from 58% to 78%. 2,14,31 We found documentation to be highest on PW, where pain scores are obtained with routine vital signs every 4-hours; however, maximum scores differed between child/caregiver and chart significantly. Although correct use of validated pain measures is expected in clinical settings, healthcare professionals may have relied on their own overall impression of the child's pain rather than involving the child/caregiver in pain assessment and using validated scales.…”
Section: Pain Assessmentmentioning
confidence: 73%
See 3 more Smart Citations